"I don't understand what you're saying now, but you are cute, I love you ": Global communication between South Korean gay male YouTubers and fans from overseas. Issue 6 (18th August 2021) - Lee, Jin
ABSTRACT: The increasing attention to South Korea's media cultures, originating from the global K-pop phenomenon, has extended to social media celebrities in South Korea (hereafter Korea), including LGBTQ+ YouTubers. Although these YouTubers' channels are run in Korean, it is easy to find non-Korean comments on their videos, posted by followers from overseas, with emojis like ❤ . Through comments, global fans show their support to the Korean LGBTQ+ YouTubers, and the YouTubers often engage in conversation with them by speaking and commenting in English. In this short essay, I explore global interaction between Korean gay male YouTubers and their global fans and discuss the potentials and limitations of these YouTubers' global popularity.